Preparing for Industry 4.0 – Testing Collaborative Virtual Learning Environments with Students and Professional Trainers - Schuster, Katharina; Plumanns, Lana; Groß, Kerstin; Vossen, Rene; Richert, Anja; Jeschke, Sabina (International Journal of Advanced Corporate Learning (iJAC), 2015)
In consideration of future employment domains, engineering students should be prepared to meet the demands of society 4.0 and industry 4.0 – resulting from a fourth industrial revolution. Based on the technological concept of cyber-physical systems and the Internet of Things, it facilitates – among others - the vision of the smart factory. The vision of “industry 4.0” is characterized by highly individualized and at the same time cross-linked production processes. Physical reality and virtuality increasingly melt together and international teams collaborate across the globe within immersive virtual environments. In this context, a large market arises in the field virtual trainings, which means that professional trainers need to explore the potential of new learning settings. In the context of the development from purely document based management systems to complex virtual learning environments (VLEs), a shift towards more interactive and collaborative components within higher educational e-learning can be noticed, but is still far from being called the state of the art. As a result, engineering education is faced with a large potential field of research, which ranges from the technical development and didactical conception of new VLEs to the investigation of students’ acceptance or the proof of concept of the VLEs in terms of learning efficiency. This paper presents three corresponding qualitative studies: In a series of focus groups, it was investigated which kinds of VLEs students prefer in a higher education context. Building upon the results of the focus groups, a collaborative VLE was created within the open world game Minecraft. In two different studies this VLE was tested, first by students and then by professional trainers. First screenings of the video material of the studies indicate a connection between communicational behavior and successful collaborative problem solving in virtual environments. The majority of the trainers who participated in the second study ascribe the new technological possibilities great potential and would consider using it within their own trainings.